Beyond stability: Mapping financial performance volatility and audit quality - Artiningsih, Arika; Kurniawan, Firdaus; Nugroho, Albertus Henri Listyanto (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2025)
This study examines the relationship between financial performance volatility and audit quality among non-financial firms listed on the Indonesia Stock Exchange from 2010 to 2024. Using 4,533 firm-year observations, the study examines how fluctuations in profitability, liquidity, and solvency impact the effectiveness of external audits, as measured by the absolute value of discretionary accruals. The empirical results show that volatility in all three financial dimensions is negatively associated with audit quality, indicating that firms with more unstable financial performance tend to experience lower-quality audits. Furthermore, cluster analysis reveals distinct volatility patterns that correspond to varying audit quality levels, confirming that financial stability is a significant determinant of audit risk. These findings extend Agency Theory and the Risk-Based Auditing Framework by introducing financial volatility as a key indicator of audit risk. The study provides implications for auditors, regulators, and policymakers to enhance audit planning and oversight in emerging market contexts.